Geospatial and Time Trend of Prevalence and Characteristics of Zero-Dose Children in Nigeria from 2003 to 2018 - Ryoko Sato (Vaccines, 2022)
Introduction: While recent years have observed a substantial improvement in vaccination coverage among children in developing countries, many children are still left out and remain unvaccinated. This study analyzes the trend of the prevalence and characteristics of zero-dose children in Nigeria over time. Methods: Using data from the Demographic and Health Survey in Nigeria from 2003 to 2018, I analyzed the prevalence and determinants of zero-dose children who had not received any DTP vaccine by geographical zone and over time. In addition, I conducted Blinder–Oaxaca decomposition analysis to evaluate the reasons for the change in the prevalence of zero-dose children over time. Results: The overall prevalence of zero-dose children reduced from over 60% in 2003 to 40% in 2018 in Nigeria. Rural areas had a higher prevalence of zero-dose children than urban areas and the gap was consistent over time. Southern zones consistently had a lower prevalence of zero-dose children, but northern zones observed more reductions in the prevalence of zero-dose children. The mother’s education and wealth level in a household are strongly associated with a lower likelihood of having zero-dose children. In both urban and rural areas, an improvement in the mother’s education level strongly explained the reduction in zero-dose children over time, while an increase in the wealth level also explained the reduction in zero-dose children in rural areas. Conclusions: While Nigeria has observed a substantial reduction in the prevalence of zero-dose children in the 15 years since 2003, the pattern of and explanatory factors for the reduction differ by geographical region. This analysis can be useful for identifying a targeting strategy to further reduce the prevalence of zero-dose children in Nigeria in the future.